Craggie bloomery: iron working in late medieval Sutherland - Atkinson, John A; Wombell, John; Miller, Jennifer; Rennie, Christine; McSwan, Gillian (Proceedings of the Society of Antiquaries of Scotland, 2016)
This note details the discovery and partial excavation of a bloomery furnace near Craggie Cottage in Glen Oykel, Sutherland, in 2010. Evidence from the excavation casts light on bloomery iron working tradition and dates the use of the furnace to the late 15th–early 17th centuries.